Keras 2.x projects : 9 projects demonstrating faster experimentation of neural network and deep learning applications using Keras /: 9 projects demonstrating faster experimentation of neural network and deep learning applications using Keras. (2018) - Ciaburro, Giuseppe
No abstract available